Pengaruh PDRB, Pendidikan, Pengangguran dan Jumlah Penduduk terhadap Kemiskinan di Kota Banjarmasin - Darmawan, Muhammad Ricky; Rusdiansyah (PPJP ULM, 2019)
This study suggests the effect of gross regional domestic product, mean yearsschool, open unemployment, and population to the poverty line in Banjarmasin City in2007-20l7. Poverty is one of the problems in economic development. Therefore in thisstudy, measuring the effect of poverty line and the factors that influence it can befound in the solution and appropriate policies to overcome poverty in Banjarmasin.The scope of this study covers the conditions of poverty in Banjarmasin City.By analyzing for ten years. The analytical method used is the method of multiplelinear regression analysis. By using the R-Square Test (R2), Simultaneous Test (FTest), and Individual Test (t-Test).The study results influence the gross regional domestic product, the averagelength of the school, the open unemployment rate, and population togethersignificantly affect poverty in Banjarmasin City.